Humanism, universities, and Jesuit education in late Renaissance Italy - Grendler, Paul F. 1936- (History of early modern educational thought, 2022)
An authoritative account of the intellectual and educational history of the late Italian Renaissance. Twenty essays on major themes, institutions, and persons of the Italian Renaissance by one of its most distinguished living historians.